Answer:
g(x) = -(0.5)^(x + 1) + 3
Explanation:
First, let's define the transformations used in this case:
Horizontal shift (horizontal translation):
If we have a function f(x), a horizontal translation can be written as:
g(x) = f(x - N)
if N is positive, the translation is to the right
if N is negative, the translation s to the left.
Vertical shift (vertical translation):
If we have a function f(x), a vertical translation can be written as:
g(x) = f(x) + N
if N is positive, the translation is upwards
if N is negative, the translation is downwards.
Reflection over the x-axis.
If we have a function f(x), a reflection over the x-axis is written as:
g(x) = -f(x).
Now we have the function:
f(x) = (0.5)^x
Let's apply the transformations:
"shifted to the left 1 unit"
g(x) = f(x - (-1) ) = f(x + 1)
"shifted down 3 unts"
g(x) = f(x + 1) - 3
"reflected over the x-axis"
g(x) = -( f(x + 1) - 3 ) = -f(x + 1) + 3
now we can replace the function equation here and get:
g(x) = -f(x + 1) + 3 = -(0.5)^(x + 1) + 3